Correlation between vitamin D levels and apoptosis in geriatric patients infected with hepatitis C virus genotype 4 - Gabr SA (Dove Medical Press, 2016)
Sami A Gabr,1,2 Ahmad H Alghadir,1 Ahmed A Allam,3,4 Jamaan Ajarem,3 Ghada Al-Basher,3 Mostafa A Abdel-Maksoud,3 Ayman A Ghfar,5 Alaa Aboud6 1Rehabilitation Research Chair, College of Applied Medical Sciences, King Saud University, Riyadh, Kingdom of Saudi Arabia; 2Department of Anatomy, Faculty of Medicine, Mansoura University, Mansoura, Egypt; 3Zoology Department, College of Science, King Saud University, Riyadh, Saudi Arabia; 4Zoology Department, Faculty of Science, Beni-Suef University, Beni Suef, Egypt; 5Department of Chemistry, College of Science, King Saud University, Riyadh, Saudi Arabia; 6Internal Endemic Medicine Department, College of Medicine, Beni-Suef University, Beni Suef, Egypt Background: Vitamin D levels play a pivotal role in most biological processes and differ according to age. A deficiency of vitamin D in chronic hepatitis C (CHC) patients has been shown to be linked with the severity of liver fibrosis, but little is known about the mechanism of this association. Objective: In this study, we evaluate the potential interrelation between vitamin D levels, oxidative stress, and apoptosis, based on liver fibrosis in geriatric patients infected with hepatitis C virus (HCV) genotype 4. Subjects and methods: A total of 120 adult individuals aged 30–68 years were recruited in this study. Of these, 20 healthy subjects (15 men and five women) with a mean age of 48.3±6.1 years were selected as controls, and 100 patients with a mean age of 47.8±4.9 years with chronic HCV (CHC) who had undergone liver biopsy (80 men and 20 women) were included in this study. Based on liver radiographic (computed tomography, magnetic resonance imaging) and histological Metavir system analyses, the CHC patients were classified into three groups: asymptomatic CHC carriers (n=30), fibrosis (n=25), and cirrhosis (n=45). HCV RNA, HCV genotypes, inflammatory cytokines AFP and TNFα, 25-hydroxyvitamin D (25[OH]D) levels, apoptotic markers single-stranded DNA (ssDNA) and soluble Fas (sFas), and oxidative stress markers nitric oxide (NO) and total antioxidant capacity (TAC) were estimated by using molecular, immunoassay, and colorimetric techniques. Results: Approximately 30% of the study population (n=30) were diagnosed as asymptomatic CHC carriers, and 70% of the study population (n=70) had severe fibrosis; these were classified into fibrosis and cirrhosis. There was a significant reduction in 25(OH)D levels and TAC activity, along with an increase in levels of NO, AFP, TNFα, ssDNA, and sFas in fibrosis and cirrhosis subjects compared with those of asymptomatic CHC carriers and health controls. The deficiency in 25(OH)D levels correlated positively with sFas, ssDNA, AFP, TNFα, NO, and TAC, and negatively with age, sex, liver function, body mass index, homeostatic model assessment – insulin resistance, HCV RNA, and viral load. Significant intercorrelation was reported between serum 25(OH)D concentrations and apoptotic and oxidative markers, which suggested progression of liver pathogenesis and fibrogenesis via oxidative and apoptotic mechanisms. Conclusion: The data showed that vitamin D status was significantly correlated with pathogenesis and fibrogenesis of the liver in geriatric patients infected with HCV genotype 4. The deficiency in 25(OH)D levels was shown to have a pivotal role in the pathogenesis of liver via apoptotic, oxidative stress, and inflammatory mechanistic pathways. The data point to adequate vitamin D levels being recommended for a good response to treatment strategies, especially in older CHC patients. Keywords: 25(OH)D, HCV, apoptosis, Fas antigen, liver fibrosis, oxidative stress, geriatrics